2019
DOI: 10.14295/cs.v9i4.1961
|View full text |Cite
|
Sign up to set email alerts
|

Interference of volunteer corn on soybean cultivars growth and yield

Abstract: Article AbstractSpontaneous corn plants in soybean crop are considered weeds because they compete for the same environmental resources. The objective of this study was to evaluate the competitive ability of soybean cultivars when in coexistence with spontaneous corn plants.A field experiment was conducted in CCGLTEC, Cruz Alta/RS, in 2014/15, in a split-plot design, with the main plot being composed of four different cultivars (CD 2694, BMX 7166, TEC 5718, TEC 6029) and the subplots of interference conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…However, lower control obtained by haloxyfop-P-methyl, pinoxaden, and cloransulam-methyl herbicides increased the corn-soybean interference effects and reduced the INP and BNP strongly, with values 18 and 55% lower than Enlist TM soybean without Enlist TM volunteer corn (Table 2). The corn-soybean competition due to inadequate control affects reproductive structures' development, with values up to 80% lower depending on the soybean cultivar used (Caratti et al 2018). These results show the importance of ensuring highest levels of control of Enlist TM volunteer corn, reducing the interference, and protecting the grain yield potential.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, lower control obtained by haloxyfop-P-methyl, pinoxaden, and cloransulam-methyl herbicides increased the corn-soybean interference effects and reduced the INP and BNP strongly, with values 18 and 55% lower than Enlist TM soybean without Enlist TM volunteer corn (Table 2). The corn-soybean competition due to inadequate control affects reproductive structures' development, with values up to 80% lower depending on the soybean cultivar used (Caratti et al 2018). These results show the importance of ensuring highest levels of control of Enlist TM volunteer corn, reducing the interference, and protecting the grain yield potential.…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, PH of Enlist TM soybean was 10% higher after exposure to cloransulam-methyl, imazethapyr, and clethodim herbicides than control (weed-free), demonstrating the need for adequate management to avoid the adverse effects of corn-soybean competition. The coexistence of glyphosate-tolerant volunteer corn in competition with soybean increased 16% the PH, especially on varieties with short growth cycle and control performed later (Caratti et al 2018). Morphological and physiological changes due to the neighbor's competition can occur between species in response to the light perception and its effects on antioxidant machinery, affecting the architecture of the canopy and photosynthetic efficacy (Benemann et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated high maize interference capacity in soybean crops (Marquardt, Krupke, & Johnson, 2012;Caratti et al, 2019), although little information is available for the Cerrado biome in Brazil. Moreover, most competition assessments link only the density of voluntary maize plants to interference potential in soybean crops, and do not evaluate possible additional maize damage from maize plant positioning in relation to soybean crop rows.…”
Section: Introductionmentioning
confidence: 99%